2022
DOI: 10.3390/su142416544
|View full text |Cite
|
Sign up to set email alerts
|

Competency-Based E-Learning Systems: Automated Integration of User Competency Portfolio

Abstract: In today’s learning environment, e-learning systems are becoming a necessity. A competency-based student portfolio system is also gaining popularity. Due to the variety of e-learning systems and the increasing mobility of students between different learning institutions or e-learning systems, a higher level of automated competency portfolio integration is required. Increasing mobility and complexity makes manual mapping of student competencies unsustainable. The purpose of this paper is to automate the mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…Analysing the research devoted to AI-based methodology in higher education, it was found that six teaching approaches are effectively applied. They include: differentiated instruction (Büyüksoy et al, 2020;Eikeland & Ohna, 2022), student-centered approach (Kerimbayev et al, 2023;Liao et al, 2021), technology-based approach (Kozlova & Pikhart, 2021;Zawacki-Richter et al, 2019), group learning (Kim et al, 2022b;Seo at al., 2021;Tan et al, 2022), game-based learning (Priyaadharshini et al, 2020;Videnovik et al, 2023), and competency-based approach (Margienė et al, 2022;Oroszi, 2020). Figure 2 shows the teaching approached in higher education with AI.…”
Section: Research Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysing the research devoted to AI-based methodology in higher education, it was found that six teaching approaches are effectively applied. They include: differentiated instruction (Büyüksoy et al, 2020;Eikeland & Ohna, 2022), student-centered approach (Kerimbayev et al, 2023;Liao et al, 2021), technology-based approach (Kozlova & Pikhart, 2021;Zawacki-Richter et al, 2019), group learning (Kim et al, 2022b;Seo at al., 2021;Tan et al, 2022), game-based learning (Priyaadharshini et al, 2020;Videnovik et al, 2023), and competency-based approach (Margienė et al, 2022;Oroszi, 2020). Figure 2 shows the teaching approached in higher education with AI.…”
Section: Research Resultsmentioning
confidence: 99%
“…According to Margienė et al (2022), Oroszi (2020), and Sistermans (2020), the competency-based approach means using outcome-based practice and it is aimed towards the increase of knowledge, skills, and values required for carrying out professional tasks adequately. The competence-based approach focuses on development and assessment of professional skills and competencies of future specialists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations